Fecal microbiota monitoring in elite soccer players along the 2019-2020 competitive season - Viciani, E.; Barone, M.; Bongiovanni, T.; Quercia, S.; Di Gesu, R.; Pasta, G.; Manetti, P.; Iaia, F. M.; Trecroci, A.; Rampelli, S.; Candela, M.; Biagi, E.; et al. (International Journal of Sports Medicine, 2022)
Physical exercise affects the human gut microbiota, which in turn influences athletes` performance. The current understanding of how the microbiota of professional athletes changes along with different phases of training is sparse. We aim to characterize the fecal microbiota in elite soccer players along with different phases of a competitive season using 16 S rRNA gene sequencing. Fecal samples were collected after the summer off-season period, the pre-season retreat, the first half of the competitive season, and the 8 weeks of COVID-19 lockdown that interrupted the season 2019-2020. According to our results, the gut microbiota of professional athletes changes along with the phases of the season, characterized by different training, diet, nutritional surveillance, and environment sharing. Pre-season retreat, during which nutritional surveillance and exercise intensity were at their peak, caused a decrease in bacterial groups related to unhealthy lifestyle and an increase in health-promoting symbionts. The competitive season and forced interruption affected other features of the athletes` microbiota, i.e., bacterial groups that respond to dietary fiber load and stress levels. Our longitudinal study, focusing on one of the most followed sports worldwide, provides baseline data for future comparisons and microbiome-targeting interventions aimed at developing personalized training and nutrition plans for performance maximization.